Occupational Allergy to Peach (Prunus persica) Tree Pollen and Potential Cross-Reactivity between Rosaceae Family Pollens - Nannan Jiang; Jia Yin; Philip Mak; Liping Wen (Iranian Journal of Allergy, Asthma and Immunology, 2015)
Orchard workers in north China are highly exposed to orchard pollens, especially peach and other Rosaceae family pollens during pollination season. The aim of this study was to investigate whether occupational allergy to peach tree pollen as a member of Rosaceae family is IgE-mediated and to evaluate the cross-reactivity among Rosaceae family pollens. Allergen skin test and conjunctival challenge test were performed; enzyme linked immune-sorbent assay (ELISA), inhibiting ELISA, western immunoblotting and inhibiting western immunoblotting were done with Rosaceae family orchard pollens, including peach, apricot, cherry, apple and pear tree pollens. Mass spectrometry was also performed to probe the main allergen component and cross-reactive protein. Sensitizations to peach pollen were found in both skin test and conjunctival challenge in the patients. Serum specific IgE to three pollens (peach, apricot and cherry) were detected through ELISA. When peach pollen used as solid phase, ELISA inhibition revealed other four kinds of pollens capable of inducing partial to strong inhibitions (45% to 87%), with the strongest inhibition belonging to apricot pollen (87%). Western   blotting showed predominant IgE binding to a 20 KD protein among these pollens, which appeared to be a cross-reactive allergen component through western blotting inhibition. It was recognized as a protein homologous to glutathione s-transferase 16 from Arabidopsis thaliana. Peach and other Rosaceae family tree pollen may serve as a potential cause of IgE mediated occupational respiratory disease in orchard workers in north China.